Professional Judgment Auditor dalam Menentukan Kecukupan Bukti Audit atas Akun Pendapatan Pada KAP SS - Rosyidah, Alim Matur; Wijaya, Raden Muhammad Syah Arief Atmaja (Jurusan Akuntansi Politeknik Negeri Padang, 2025)
This study aims to obtain empirical evidence regarding the application of professional judgment by auditors in assessing the sufficiency of audit evidence on revenue accounts to prevent the risk of material misstatement. This study uses a qualitative approach with a case study at KAP SS. Data was collected through semi-structured interviews with two auditors. The results of the study indicate that revenue accounts have a high risk of misstatement, thus requiring the application of careful judgment. Auditors consider various factors in determining the sufficiency of evidence, such as materiality level, audit risk, economic conditions, as well as the size and characteristics of transactions. The audit procedures used include substantive testing and control testing with adjustments to procedures based on identified risks. The application of professional judgment is also reinforced through a system of supervision and collaboration among auditors. This study emphasizes that professional judgment plays an important role in making appropriate audit decisions, maintaining the integrity of financial statements, and ensuring that the evidence obtained is sufficient, relevant, and reliable in supporting the auditor's opinion.